1964
DOI: 10.1175/1520-0493(1964)092<0207:incava>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ice Nucleus Counts and Variations at 3.4 Km. And Near Sea Level in Hawii

Abstract: Concurrent ice nucleus counts made twice daily at M a m a Loa Observatory (3.4 h i .) and near sea level at Hilo, Hawaii, from December 1, 1061, to February 5 , 1062, and :it intervals of a few minutes during 24 hours on July 10-11, 1963, indicated thc wide fluctuations observed elsewhere, with counts varying not oiily from day to day, but by as mnch as an order of magnitude within minutes. Background levels at M a m a Loa Observatory ran mcll below those a t Hilo and averaged tinder 10 ice crystals in 10 lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Equally low or very much lower values have been reported in the maritime airmasses, as for example, less than 100 per cubic metre at -20°C in the air from the Pacific Ocean (Isono et al, 1959), 500 per cubic metre at -24°C in Hawaii (Price and Pales, 1964) and less than 2 per litre at -18 °C at Eskdalemiur in England (Stevenson 1968). The question which, however, arises in this context is about the source region of these nuclei in the maritime air.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Equally low or very much lower values have been reported in the maritime airmasses, as for example, less than 100 per cubic metre at -20°C in the air from the Pacific Ocean (Isono et al, 1959), 500 per cubic metre at -24°C in Hawaii (Price and Pales, 1964) and less than 2 per litre at -18 °C at Eskdalemiur in England (Stevenson 1968). The question which, however, arises in this context is about the source region of these nuclei in the maritime air.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have been made tracing the origin of the natural ice-forming nuclei to the sea (Brier and Kline;1959;Battan and Riley, 1960), to the land (Isono et al 1959;Price and Pales, 1964), to the stratosphere (Bigg and Miles, 1963) and to extra terrestrial sources (Maruyama and Kitagawa, 1967). Based on measurements made at Delhi (28°35' N, 77°12' E, 210 meters A.M.S.L.)…”
Section: Introductionmentioning
confidence: 99%
“…There are conflicting views in the literature regarding the effectiveness of volcanic ash as IN, with some investigators concluding that volcanic emissions contain abundant IN [ Hobbs et al , 1971b; Isono and Ikebe , 1960; Isono et al , 1959a, 1959b] and others who suggest the opposite [ Langer et al , 1974; Price and Pales , 1964; Pueschel and Mendonca , 1972; Schnell and Delany , 1976; Schnell et al , 1982]. One difficulty with some of the latter studies relates to an inadequacy in the “membrane filter” measurement technique used, which biases measurements toward an underestimate of IN concentrations [ Hussain and Saunders , 1984].…”
Section: Measurements Of Volcanic Ice Nucleimentioning
confidence: 99%
“…Active volcanoes have been suggested as being sources of atmospheric ice nuclei (IN) [Isono et al, 1959;Hobbs et al, 1971;Tanaka, 1980], the relatively rare aerosol particles that are thought to initiate much of the Earth's precipitation. Other researchers have indicated that at least some active volcanoes are not releasing IN to the atmosphere [Price and Pales, 1964;Pueschel and Mendonca, 1972;Schnell and Delaney, 1976].…”
Section: Introductionmentioning
confidence: 99%